The Effect of Bullying on Self-Esteem of Grade X Students - Yuhana Silvi; Rici Kardo; Suryadi (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the presence of several students who feel isolated, afraid to try new things, feel low in self-confidence, feel unappreciated, experience long-term emotional impacts such as depression, and frequently skip or miss classes. Several students who feel isolated, afraid to try new things, feel low in self-confidence, feel unappreciated, experience long-term emotional impacts such as depression, and often skip or miss classes. This study aims to determine: 1) Bullying behavior in class X at SMA Negeri 1 Ranah Batahan. 2) Self-esteem of class X students at SMA Negeri 1 Ranah Batahan. 3) Examine the Effect of Bullying on Self-esteem in Class X students at SMA Negeri 1 Ranah Batahan. This study used a quantitative research method using simple linear regression analysis. The population was 75 students, with a total sampling technique. The instrument used in this study was a questionnaire. Data analysis in this study used percentages and simple linear regression. The results of this study indicate: 1) Bullying among 10th-grade students at SMA Negeri 1 Ranah Batahan is in the high category. 2) Self-esteem among 10th-grade students at SMA Negeri 1 Ranah Batahan is in the low category. 3) Bullying has a 9% effect on 10th-grade students' self-esteem. The results indicate that bullying has a negative effect on self-esteem in 10th-grade students at SMA Negeri 1 Ranah Batahan, with a very low coefficient of 9%. The higher the level of bullying, the lower the students' self-esteem. This study shows that students who experience high levels of bullying tend to have low self-esteem. Therefore, efforts are needed to address bullying in students to improve their self-esteem. This study is recommended to principals, guidance counselors, and students to prevent bullying and improve their self-esteem.